“仁者壽”: 儒家的德性健康之醫學模式: The Benevolent Enjoy Longevity: A Model of Medicine Based on Confucian Virtues - CAO, Yongfu (International Journal of Chinese & Comparative Philosophy of Medicine, 2015)
LANGUAGE NOTE | Document text in Chinese; abstract in English only. Professor Lee Shui Chuen’s article addresses a very interesting Confucian medical model. He puts forth the Confucian concepts of soul disease and soul health, which are worthy of broader attention. In this response, I discuss the related issues of how an individual can suffer disease from a lack of virtue or lack health owing to a failure to cultivate virtue. I hold that such Confucian ideas—disease and health in relation to virtue—should be important parts of soul disease and soul health in the Confucian medical model that Lee lays out. Indeed, as Lee points out, behavior that violates virtue in the sense of harming the interests of others or damaging relationships is often seen as “ill” conduct in Confucian culture. Such conduct is inevitably related to mental health and spiritual development, and can thus influence life quality and expectancy. It is a Confucian belief that the virtuous and benevolent enjoy longevity. DOWNLOAD HISTORY | This article has been downloaded 49 times in Digital Commons before migrating into this platform.